Pemberdayaan Kelompok Wanita Tani Berbasis Urban Farming di Kelurahan Malaka Sari dalam Peningkatan Kesejahteraan Keluarga - Woro Harkandi Kencana; Meisyanti Meisyanti; Yunita Sari (Universitas Muhammadiyah Surakarta, 2022)
Women Farmers Group (KWT) is a forum that provides opportunities for women to participate in advancing the agricultural sector. KWT D’Shafa as a PKM activity partner is a forum for women in the Duren Sawit area of East Jakarta based on urban farming. Apart from this, KWT D’Shafa also has a business sector for processing crops and catering. Problems with this KWT include: the minimum number of KWT members; management of potential urban farming land that has not been utilized optimally; limited knowledge of KWT members in business management knowledge; the system for recording partner members, harvests, and product sales is still manual; lack of partner knowledge about appropriate marketing communications in promoting KWT D’Shafa and the results of urban farming management. Community service activities are carried out by socializing the existence of partners and the benefits of urban farming in the community. Making hydroponic installations is carried out in the management of potential urban farming land. Then training activities and business management assistance are carried out to maximize crop yields and processed products into economic and productive value. The system for recording partner members, harvests, and product sales uses a web-based application, namely the Google Site, which is effective and efficient. The next activity is marketing communication training, especially appropriate digital marketing in promoting the D’Shafa Women’s Farmer Group and the results of urban farming management. The digital platforms managed by KWT D’Shafa in this activity include websites and social media (Instagram, Facebook, Tik Tok and Youtube). With this PKM activity, it is able to improve the welfare of the KWT D’Shafa family.